2006
DOI: 10.1111/j.1469-8137.2006.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of late stage flower development in Primula vulgaris reveals novel differences in cell morphology and temporal aspects of floral heteromorphy

Abstract: Summary• Heterostyly in Primula is characterized by the development of long-styled pin and short-styled thrum flowers, with anthers midway down the corolla tube in pin flowers, and at its mouth in thrum flowers. Other differences include pollen size and stigmatic papillae length. Several linked genes at the S locus control these differences.• In this study we have analyzed pin and thrum flowers through the temporal development of heteromorphy.• These studies indicate that the S locus linked genes that orchestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Cell division and cell elongation could contribute to the growth of floral organs [11], [16], [20]. Different microscopic patterns of floral development were found in some distylous species with tubular corolla, which showed cell division mainly served to influence anther height in two morphs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell division and cell elongation could contribute to the growth of floral organs [11], [16], [20]. Different microscopic patterns of floral development were found in some distylous species with tubular corolla, which showed cell division mainly served to influence anther height in two morphs.…”
Section: Discussionmentioning
confidence: 99%
“…Styles and petal tubes with attached anthers of L- and S-morph flowers of P. veris were sampled when petals were between 4 and 10 mm long, corresponding to the time when the difference in style length and anther position develops (Stirling, 1932; Webster and Gilmartin, 2006). Three replicate samples were collected per morph and organ, pooling organs of 25 plants per sample.…”
Section: Methodsmentioning
confidence: 99%
“…Heterostyly in Primula is controlled by the S -locus supergene that likely comprises five tightly linked genes, determining style length (the so-called G locus), anther height, pollen size and male and female intra-morph incompatibility (Figure 1A; Figure 1—figure supplement 1) (Ernst, 1936; Lewis and Jones, 1992). The S-morph haplotype carries dominant alleles at all loci, resulting in short styles due to reduced cell elongation (Webster and Gilmartin, 2006) and anthers at the mouth of the flower; the L-morph haplotype carries the recessive alleles, causing long styles and low anthers. S-morphs are heterozygous for the two haplotypes, and L-morphs homozygous recessive; the absence of homozygotes for the S-morph haplotype likely results from a recessive lethal mutation on this haplotype (Kurian and Richards, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A study in tristylous Pontederia cordata (Richards and Barrett 1987) also suggested that ''morph-dependent variation in stigma height depends on differences in style length, not ovary length.'' Furthermore, longer style cells in pin than in thrum may have contributed to the differentiation of the style length as seen in distylous Primula vulgaris (Heslop-Harrison et al 1981;Webster and Gilmartin 2006).…”
Section: Differentiation Of Pin and Thrum In Distylymentioning
confidence: 96%